Rational use of antibacterials in pleural empyema (One Health & Risk Management, 2024)
Introduction. Pleural empyema remains a significant cause of morbidity and mortality globally. The rising incidence of this complex pathology necessitates an evaluation of diagnostic methods, surgical treatment, and antibiotic therapy strategies. Material and methods. We selected and analyzed 50 observation records of patients with pleural empyema admitted to the thoracic surgical ward at Timofei Mosneaga Republican Clinical Hospital. A literature review was conducted to elucidate the rationale behind the administration of antibacterial treatment. Results. Bacteriological examination of the pleural fluid revealed the presence of pathogenic flora, predominantly gram-negative (15 cases) - P. aeruginosa, Acinetobacter, K. pneumoniae, E. aerogenes, S. marcescens, Corrynebacterium, P. mirabilis, and in 5 cases, a polymicrobial etiology was observed. Evaluation of microbial susceptibility allowed for a rational choice of antibacterial treatment. Beta-lactam antibiotics were most frequently administered, either in monotherapy or in combination. Other groups of antibacterials administered included fluoroquinolones, aminoglycosides, macrolides, polymyxins, nitroimidazole derivatives, and glycopeptides. Conclusions. Effective and harmless antibacterial treatment can only be achieved by identifying the causative pathogens and their antimicrobial susceptibility, ensuring adequate concentrations in the pleural space, determining the routes of administration, the duration of therapy, and the rational combination of antimicrobials.